A Step Ahead : Competition Policy for Shared Prosperity and Inclusive Growth - World Bank; Organisation for Economic Co-operation and Development (Washington, DC: World Bank, 2017)
Sustainable economic development has played a major role in the decline of global poverty in the past two decades. There is no doubt that competitive markets are key drivers of economic growth and productivity. They are also valuable channels for consumer welfare. Competition policy is a powerful tool for complementing efforts to alleviate poverty and bring about shared prosperity. An effective competition policy involves measures that enable contestability and firm entry and rivalry, while ensuring the enforcement of antitrust laws and state aid control. Governments from emerging and developing economies are increasingly requesting pragmatic solutions for effective competition policy implementation, as well as recommendations for pro-competitive sectoral policies.